2019
DOI: 10.3390/molecules24050900
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antimicrobial Activity of Essential Oils against Salmonella enterica Serotypes Enteritidis and Typhimurium Strains Isolated from Poultry

Abstract: Salmonella enterica serotype Enteritidis and S. enterica serotype Typhimurium are frequently present among poultry and are associated with outbreaks of human salmonellosis. The study investigated the in vitro antimicrobial activity of essential oils (EOs) obtained from Aloysia triphylla, Cinnamomum zeylanicum, Cymbopogon citratus, Litsea cubeba, Mentha piperita, Syzygium aromaticum against S. Enteritidis and S. Thyphimurium strains previously isolated from poultry. A 1:1 mixture of C. zeylanicum and S. aromati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 26 publications
4
28
0
1
Order By: Relevance
“…Similar composition was reported in other studies 37,38. In Italian MPEO, menthol (32.4%) and menthone (26.6%) were determined,39 while linalool and linalyl acetate were detected as major compounds of Tunisian MPEO 40…”
Section: Discussionsupporting
confidence: 85%
“…Similar composition was reported in other studies 37,38. In Italian MPEO, menthol (32.4%) and menthone (26.6%) were determined,39 while linalool and linalyl acetate were detected as major compounds of Tunisian MPEO 40…”
Section: Discussionsupporting
confidence: 85%
“…isolated from human patients, with MIC values higher (35-140 mg/mL) than the value observed in the present study. Moreover, this EO showed a good activity against Aspergillus fumigatus in a previous study [49] and a poor effectiveness versus the probiotic yeast Saccharomyces cerevisiae [50], indicating a variable efficacy against different species of both molds and yeasts. The antifungal activity seems to be related to a higher content of limonene and sabinene, in comparison with the other EOs.…”
Section: Discussionmentioning
confidence: 76%
“…These results are in agreement with findings reported by Bismarck et al [52] and Sim et al [56] in otologic canine isolates. This EO, in fact, although poorly effective against molds such as A. fumigatus [49] and dermatophytes [55], showed a strong antimicrobial activity versus Salmonella enterica serotype Typhimurium and Escherichia coli isolated from poultry [50].…”
Section: Discussionmentioning
confidence: 99%
“…In a different application, the EO of thyme in combination with cold plasma treatment led to a higher antibacterial activity of plasma-treated nanofibers ( Lin et al., 2019 ). Essential oils could be applied for the purposes of facility disinfection, as well as added to chicken feed to prevent intestinal colonization with pathogens ( Ebani et al., 2019 ). The antimicrobial activity data for EO showed that thymol, eugenol, and carvacrol exhibit strong antimicrobial activity against both E. coli and S. typhimurium ( Franz and Baser, 2010 , Hippenstiel et al., 2011 , Bassole and Juliani, 2012 ).…”
Section: Resultsmentioning
confidence: 99%